(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
According to the statistical data of pathological examination, the frequency of detection of spinal cord tumors is 10-15% of all tumors of the central nervous system (CNS) [1,2,3]. Most often, spinal cord tumors (SCT) are observed in the socially active group of people aged 30-50 years, which determines the great relevance of this problem [2,4,5]. Tumors of the cervical spinal cord account for 19.0-36.5%, thoracic - 26.9-47.0%, lumbosacral - 23.0-33.3%, equine tail and terminal thread - 11%. The most common are extramedullary tumors 53-90% of all spinal cord tumors, the frequency of intradural intramedullary tumors is 10-30%. With the introduction of modern neuroimaging methods of research (magnetic resonance imaging, multispiral computed tomography) into neurosurgical practice, the diagnosis of spinal cord tumors has improved significantly. However, the problem of timely detection of spinal cord tumors remains relevant everywhere, which determines the results of surgical interventions [3,4,5].